Photoelectrochemical water splitting over mesoporous CuPbI3 films prepared by electrophoretic technique - Naeem, R. (Springer-Verlag Wien, 2017)
Abstract: Copper lead iodide, CuPbI3, nano powder has been synthesized by co-precipitation of PbI2 on aqueous suspension of CuI followed by solid-state chemical reaction; its film was fabricated on FTO substrates by electrophoretic deposition technique and tested for photoelectrochemical water splitting using solar light. The synthesized CuPbI3 nano powder has been characterized by thermogravimetric, differential thermal analysis, differential scanning calorimetry, and X-ray diffraction. The surface morphology and the elemental composition of the electrophoretically deposited film have been characterized by XRD, Raman spectroscopy, X-ray photoelectron spectroscopy, field emission scanning electron microscope, and energy dispersive X-ray mapping. The direct band gap energy of CuPbI3 film of average thickness 96 μm has been estimated at 1.82 eV and the film shows a current density of 216 µA/cm2 at 0.62 V measured in 0.1 M Na2SO4 solution vs. Ag/AgCl/3 M KCl. This study explores the viability of synthesis of a variety of inorganic halide photocatalysts for enhanced stability and improved solar capturing. Graphical abstract: Figure not available: see fulltext.. © 2017, Springer-Verlag Wien.